2011
DOI: 10.1002/jcb.23270
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by heat shock protein 20 of hepatocellular carcinoma cell proliferation via inhibition of the mitogen‐activated protein kinases and AKT pathways

Abstract: Heat shock protein (HSP) 20, one of the low-molecular weight HSPs, is known to have versatile functions, such as vasorelaxation. However, its precise role in cancer proliferation remains to be elucidated. While HSP20 is constitutively expressed in various tissues including the liver, we have previously reported that HSP20 protein levels in human hepatocellular carcinoma (HCC) cells inversely correlate with the progression of HCC. In this study, we investigated the role of HSP20 in HCC proliferation. The activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 49 publications
2
52
1
Order By: Relevance
“…For example, the expression of HSPB6 in human HCC cells inversely correlated with the TNM stage. HSPB6 reportedly inhibited the proliferation of HCC cells via suppression of the MAPK family, including JNK and the PI3K/Akt pathway [84,85]. Furthermore, in consistent with the previous result that HSPB6 inhibited LPS-induced NF-κB activation in cardiomyocytes, HSPB6 acts as a negative regulator of HCC via down-regulation of TNF-α-stimulated IKK/IκB/NF-κB pathway [86].…”
Section: Role Of Hspb6 In Cancersupporting
confidence: 75%
“…For example, the expression of HSPB6 in human HCC cells inversely correlated with the TNM stage. HSPB6 reportedly inhibited the proliferation of HCC cells via suppression of the MAPK family, including JNK and the PI3K/Akt pathway [84,85]. Furthermore, in consistent with the previous result that HSPB6 inhibited LPS-induced NF-κB activation in cardiomyocytes, HSPB6 acts as a negative regulator of HCC via down-regulation of TNF-α-stimulated IKK/IκB/NF-κB pathway [86].…”
Section: Role Of Hspb6 In Cancersupporting
confidence: 75%
“…We have previously shown that HSP20 suppresses HCC cell growth by downregulation of proliferation signals via the AKT and mitogen-activated protein kinase pathways (11,12). Cell growth is affected by both the survival and apoptosis signals.…”
Section: Discussionmentioning
confidence: 99%
“…These cells were established as described previously, by means of Tet-Off™ gene expression systems (Clontech Laboratories Inc., Palo Alto, CA, USA) according to the manufacturer's instructions (11). Induction of HSP20 protein expression in the HSP20-overexpressing cells can be controlled by the presence of doxycycline (Sigma-Aldrich).…”
Section: Stable Transfectionsmentioning
confidence: 99%
See 2 more Smart Citations